2008
DOI: 10.1136/gut.2007.142778
|View full text |Cite
|
Sign up to set email alerts
|

Integrin-linked kinase regulates cell proliferation and tumour growth in murine colitis-associated carcinogenesis

Abstract: From these findings, it is concluded that ILK plays an important role in intestinal epithelial cell proliferation, and that it influences the development of colitis-associated cancer, through modulation of cyclin D1, the extracellular matrix and MMP9.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
44
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 37 publications
6
44
0
Order By: Relevance
“…Our data indicated that absence of Jak3 expression resulted in shortened colon length, reduced colon to body weight ratio, and reduced cecum length in untreated mice. Although several studies indicated reduced colonic length post-DSS-induced colitis, it was not known if reduced colon length predisposes toward colitis (40,41). We showed that Jak3-deficient mice had reduced colon length, and when these mice were subjected to DSS-induced colitis, they developed more severe colitis symptoms than their WT counterparts suggesting that Jak3 played a protective role during DSS-induced colitis (Fig.…”
Section: Discussionmentioning
confidence: 67%
“…Our data indicated that absence of Jak3 expression resulted in shortened colon length, reduced colon to body weight ratio, and reduced cecum length in untreated mice. Although several studies indicated reduced colonic length post-DSS-induced colitis, it was not known if reduced colon length predisposes toward colitis (40,41). We showed that Jak3-deficient mice had reduced colon length, and when these mice were subjected to DSS-induced colitis, they developed more severe colitis symptoms than their WT counterparts suggesting that Jak3 played a protective role during DSS-induced colitis (Fig.…”
Section: Discussionmentioning
confidence: 67%
“…For instance, Neu-oncogene-induced mammary-tumor formation is dramatically delayed in the ILK-null genetic background (Bill Muller, McGill University, Quebec, Canada, personal communication). Similarly, carcinogen-induced and colitisassociated intestinal-tumor formation is markedly diminished in the absence of ILK (Assi et al, 2008). The mechanism of action of ILK in cancer cells remains to be fully elucidated; however, substantial downregulation of phosphorylation of Akt at Ser473 has been observed in the mammary-tumor model and diminished cyclin-D expression has been reported in the intestinal model, which suggests that ILK-mediated cell survival is at least a part of the story.…”
Section: Genetic Inhibition Of Ilk Function In Cancer Cellsmentioning
confidence: 97%
“…Because of the short turnover cycle of the gastric pit cells, the proliferation of progenitor cells and the apoptosis of mature pit cells need to be tightly controlled in order to maintain homeostasis of the gastric mucosa. Dysfunction of gastric pit cells has been reported to be involved in various gastric disorders, including atrophic gastritis and metastatic gastric cancers (Assi et al, 2008;Fukaya et al, 2006;Galmiche et al, 2000;Kabashima et al, 2002;Peek et al, 2000;Tsutsumi et al, 2002). A recent study has shown that transcription factor foxq1 is required for the terminal differentiation of pit cells (Verzi et al, 2008).…”
mentioning
confidence: 98%